(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article explores the intersection between mental health and the work environment, analyzing the legal and psychological aspects involved. The 1988 Federal Constitution recognizes the right to a healthy working environment, but Brazilian labor legislation still has gaps in protecting workers’ mental health. The study shows that unfavorable working conditions, such as work overload and bullying, can trigger mental disorders such as anxiety, depression and Burnout Syndrome. These problems have a negative impact on productivity, increase absenteeism and generate significant costs for companies. The employer’s responsibility to ensure a safe and healthy working environment is emphasized. Brazilian legislation provides for civil and, in some cases, criminal liability for companies that fail to fulfill this obligation. However, the application of these standards still faces challenges. Organizational psychology plays a crucial role in promoting mental health at work, offering tools and strategies for creating healthier and more productive environments. Implementing wellness programs, promoting a positive organizational climate and offering psychological support are essential measures to prevent workers from becoming mentally ill.